Factors associated with the Physical Fitness of Lactating Mothers in an Urban Area - Lisnawati Naintina; Pangestuti Dina Rahayuning; Asna Alfi Fairuz; Rahfiludin Mohammad Zen; Joko Tri (BIO Web of Conferences)
An urban area is characterized by increased sedentary lifestyle (SL) and reduced physical fitness (PF) among various populations, including lactating mothers. Adequate physical fitness is essential for lactating mothers to support breastmilk production during the lactating period. This study used an observational method with a cross-sectional design that aims to analyze factors associated with physical fitness among lactating mothers in an urban area. This study included 61 lactating mothers selected through systematic random sampling in Magelang City. Physical fitness status was assessed by a six-minute walk test. Trained enumerators collected data using validated instruments for each variable. Data were analyzed using Chisquare and Fisher’s exact tests. The results showed that most subjects had moderate PF (68.3%), while only 34.9% engaged in vigorous physical activity. In addition, only 3.2% of subjects were well-hydrated, and a significant portion had inadequate calcium (76.2%) and iron (61.9%) intake. However, no significant correlation was found between physical activity, nutritional intake (total energy, calcium, and iron), hydration status, and physical fitness among the lactating mothers (p > 0.05). Therefore, future research should consider incorporating additional variables such as biochemistry and environmental factors.